Signals through gp130 upregulate bcl-x gene expression via STAT1-binding cis-element in cardiac myocytes. - Fujio, Y (1997)
We described recently the activation of the Janus kinasesignal transducer and activator of transcription (JakSTAT) and mitogen-activated protein (MAP) kinase pathways by leukemia inhibitory factor (LIF) through gp130, a signal transducer of IL-6-related cytokines, that transduces hypertrophic signals in cardiac myocytes. In addition, stimulation of gp130 by IL-6-related cytokines is known to exert a cytoprotective effect. In the present study, we investigated the possibility that activation of gp130 initiates activation of the cytoprotective genes in cardiac myocytes. Incubation of cardiac myocytes with LIF induced the expression of bcl-x, and the isoform that was induced by LIF was identified as bcl-xL. Induction of bcl-xL protein was also identified by Western blotting. Antisense oligonucleotide against bcl-x mRNA inhibited protective effect of LIF accompanied with the reduction in bclxL protein. We constructed bcl-x promoter-luciferase reporter gene plasmids (-639/+10- or -161/+10-luciferase), and transfected them to cardiac myocytes. LIF stimulation increased the luciferase activity of -639/+10-luciferase plasmids. Although -161/+10-luciferase plasmids presented comparable responsiveness to LIF, the basal transcription level was impaired. The LIF-responsive cis-element was localized to a DNA fragment (positions -161 to +10) that contains an interferon-gamma activation site (GAS) motif (GGA) at position -41 of the bcl-x gene promoter. This motif bound to STAT1, not to STAT3, and site-directed mutagenesis revealed that this motif was essential for LIF-responsive promoter activity. These data suggest that LIF induces bcl-x mRNA via STAT1 binding cis-element in cardiac myocytes, presenting cytoprotective effect.